Kristendommen og religionerne - Jenson, Robert W. (Dansk Teologisk Tidsskrift, 2009)
In the present article, Robert W. Jenson argues against the commonly used simile that all religions are only different paths leading to the top of the same mountain. Instead, it is suggested that religions should be seen as different mountains with many similar paths. From this simile, and from the Church’s founding message, it follows that the conversation between the church and the religions must be one of mission. In the course of the article Jenson discusses the relationship between reason and revelation, explains the relevance of the incarnation, and reflects upon the prospects and difficulties of Christian conversation with Islam.